Hubungan Antara Pemahaman Kompetensi Pedagogis Guru dengan Kesiapan Mengajar Microteaching Mahasiswa PIAUD IAIN Surakarta - Tirta Arum Layungsari Wibowo; Rosida Nur Syamsiyati (ABNA : Journal of Islamic Early Childhood Education, 2020)
This study aims to determine the relationship between understanding pedagogical competence and students' readiness to teach microteaching. The method used is quantitative correlational. The population in this study were all students of PIAUD IAIN Surakarta class 2017 a total of 103 students, while the sample used was 68 students who were taken using cluster random sampling technique. Data collection obtained by conducting tests and questionnaires.The results of the study using the spearman rank correlation formula and converted to the t-test yielded t count 2.3695 consulted with t table dk = n-2 = 68-2 = 66, 5% significance obtained a value of 1.6683. Based on the results of t_count (2.3695)> ttable (1.6683), it can be concluded that there is a positive relationship between understanding pedagogical competence and the readiness to teach microteaching students of PIAUD IAIN Surakarta for the 2019/2020 academic year.